1996
DOI: 10.1172/jci119035
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP is a hepatorenal link influencing natriuresis and contributing to glucagon-induced hyperfiltration in rats.

Abstract: The effects of glucagon (G) on proximal tubule reabsorption (PTR) and GFR seem to depend on a prior action of this hormone on the liver resulting in the liberation of a mediator and/or of a compound derived from amino acid metabolism. This study investigates in anesthetized rats the possible contribution of cAMP and urea, alone and in combination with a low dose of G, on phosphate excretion (known to depend mostly on PTR) and GFR. After a 60-min control period, cAMP (5 nmol/min ϫ 100 grams of body weight [BW])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 65 publications
3
40
0
Order By: Relevance
“…Increased plasma cyclic AMP levels in autism are significantly and positively associated with hyperkinesia and serum serotonin levels (Hoshino, Kumashiro et al 1979). However, since a variety of tissues contribute to plasma cAMP levels, the interpretation of plasma cAMP studies is not specific to brain (Goldberg 1984) and could be explained by alternative pathways such as hepatorenal plasma cAMP signaling (Ahloulay, Dechaux et al 1996). Although CSF and peripheral blood measures indicate that cAMP levels are normal to high in autism, the cAMP cascade remains to be studied in the autistic brain.…”
Section: Camp In Autismmentioning
confidence: 99%
“…Increased plasma cyclic AMP levels in autism are significantly and positively associated with hyperkinesia and serum serotonin levels (Hoshino, Kumashiro et al 1979). However, since a variety of tissues contribute to plasma cAMP levels, the interpretation of plasma cAMP studies is not specific to brain (Goldberg 1984) and could be explained by alternative pathways such as hepatorenal plasma cAMP signaling (Ahloulay, Dechaux et al 1996). Although CSF and peripheral blood measures indicate that cAMP levels are normal to high in autism, the cAMP cascade remains to be studied in the autistic brain.…”
Section: Camp In Autismmentioning
confidence: 99%
“…The phosphodiesterase inhibitor 3-isobutyl-1-methylxanthine (1 mmol/L) was added to all of the samples to prevent cAMP degradation. [17][18][19] After treatment, the medium was removed, and the cells were washed and lysed with 0.1 N HCl. The lysates were centrifuged at 1000g, and cAMP levels in supernatants were determined using a sensitive cAMP ELISA kit (R&D).…”
Section: Glucagon Receptor Binding and Receptor-mediated Signaling Inmentioning
confidence: 99%
“…Animal and clinical studies have shown that hyperglucagonemia plays an important role in the development of glomerular hyperfiltration and mesangial cell injury [4][5][6]29]. In rats, we found that glomerular hyperfiltration induced by glucagon was attenuated by inhibiting angiotensinconverting enzyme (ACE) with enalapril [30,31], together suggesting that glucagon interacts with Ang II to regulate glomerular filtration.…”
Section: Western Blots Of Total and Phosphorylated Erk 1/2 In Mcsmentioning
confidence: 88%